LINDA M. MORRA and JESSICA SCHAGERL, eds., Basements and Attics, Closets and Cyberspace: Explorations in Canadian Women’s Archives - Dean, Heather (Archivaria, 2013)
Basements and Attics, Closets and Cyberspace: Explorations in Canadian Women’s Archives. LINDA M. MORRA and JESSICA SCHAGERL, eds. Waterloo, ON: Wilfrid Laurier University Press, 2012. ix, 355 pp. ISBN 978-1- 55458-650-9.